THE RELATIONSHIP BETWEEN LEADERSHIP STYLE AND EMPLOYEE PERFORMANCE IN PUBLIC HEALTH CENTER KONAWE DISTRICT: LEADERSHIP STYLE AND EMPLOYEE PERFORMANCE - Marniansih Marniansih; Sanihu Munir; La Ode Kamalia (STIKes Mandala Waluya Kendari, 2022)
Background: Based on the preliminary interview, it shows that most of the employees have a less satisfied response with the existing leadership style at the Public health center and although most say that the leadership is very open to suggestions and criticism from their employees. Furthermore, the Public health center with a leadership style that according to some staff is less favorable, but has better service to the public than the Public health center with a leadership style that is preferred by its staff. So, the question is whether the influence of the leadership style carried out by the leadership of the Public health center, and the organizational culture that is formed will be able to influence the increase in employee productivity at each Public health center. Methods: This research is a quantitative using cross sectional design. The research was conducted from February to March 2021 with 124 samples. Result: It is known that there is a relationship between Authoritarian Leadership Style and Employee Performance ( X2calculation, Chi Square= 41.90> X2 table3.84), Delegation Leadership Style with Employee Performance (X2 Count or Chi Square= 57.56> from 3.84 or X2 table), Participatory leadership style with Employee Performance (X2 Count or Chi Square 26.82> of 3.84 or X2 table). Conclusion: Authoritarian Leadership Style has a strong relationship, delegation has a strong relationship, and also participation has a strong enough relationship to the performance of employees at the Konawe District Health Center.